EFEKTIVITAS PENCARIAN RUTE RUMAH KOS DAN KONTRAKAN BERBASIS ALGORITMA DIJKSTRA DAN ASTAR - Moh Nur Latuconsina (KLIK- KUMPULAN JURNAL ILMU KOMPUTER, 2021)
Today we live in a digital age, where all things in our life. Technological developments make the exchange of information so fast. How to get information is also very easy. The digital era that we are experiencing today actually goes hand in hand with the growth of the human population which is also increasing so fast. Technological sophistication has not been able to provide a significant solution regarding the need for a place to live. This has made the purchase price of a house more expensive, especially in the capital city and its surroundings. The higher the purchase price of a house makes many people prefer to live in a boarding house or rented house, this is because the rental price is relatively cheap instead of buying a house. For example, in the city of Jakarta, around the campus, there are many boarding houses and rented houses due to the large number of National University students from various regions throughout Indonesia. Therefore, in this study created a THE EFFECTIVENESS OF SEARCHING FOR KOS AND RENTAL HOUSE BASED ON THE ALGORITHM OF DIJKSTRA AND ASTAR ". This website development uses PHP language with Laravel framework and uses Atom as a text editor. This website requires an internet network to display data, view directions via google maps, and to contact the owner via whatsapp. Based on the results of testing and implementation, it can be concluded that this website was successfully created. This website can make it easier for new students of the National University of Jakarta to find boarding houses or rented houses around the campus. created. This website can make it easier for new students of the National University of Jakarta to find boarding houses or rented houses around the campus.Keywords: Dijkstra's Algorithm, Astar Algorithm, Boarding House, Website Saat ini kita hidup di era digital, di mana semua hal dalam kehidupan kita. Perkembangan teknologi membuat pertukaran informasi menjadi begitu cepat. Cara mendapatkan informasi pun sangat mudah. Era digital yang kita alami saat ini ternyata berjalan beriringan dengan pertumbuhan populasi manusia yang juga meningkat begitu cepat. Kecanggihan teknologi ternyata belum bisa memberikan solusi yang signifikan mengenai kebutuhan akan tempat tinggal. Hal tersebut membuat harga beli rumah semakin mahal terutama di kawasan Ibu kota dan sekitarnya. Harga beli rumah yang semakin tinggi membuat banyak orang lebih memilih tinggal di sebuah rumah kos ataupun rumah kontrakan hal ini dikarenakan harga sewa yang terbilang murah ketimbang membeli sebuah rumah. Sebagai contoh, di Kota Jakarta tepatnya di sekitar kampus terdapat banyak rumah kos dan rumah kontrakan dikarenakan banyaknya mahasiswa Universitas Nasional dari berbagai daerah di seluruh Indonesia. Oleh karena itu dalam penelitian ini dibuat “EFEKTIVITAS PENCARIAN RUMAH KOS DAN KONTRAKAN BERBASIS ALGORITMA DIJKSTRA DAN ASTAR”. Pembuatan website ini menggunakan bahasa PHP dengan framework Laravel dan menggunakan Atom sebagai text editor. Website ini membutuhkan jaringan internet untuk menampilkan data, melihat petunjuk arah melalui google maps, dan untuk menghubungi pemilik via whatsapp. Berdasarkan hasil uji coba dan implementasi, dapat disimpulkan bahwa website ini berhasil dibuat. Website ini dapat mempermudah mahasiswa baru Universitas Nasional Jakarta dalam mencari rumah kos atau kontrakan di sekitar kampus.Kata Kunci: Algoritma Dijkstra, Algoritma Astar, Rumah Kos, Website